Challenges in preparing and implementing project-based learning – teachers’ experience - Dušan P. Ristanović; Biljana D. Radović; Мirko S. Marković (Inovacije u Nastavi)
The essence of the project-based learning rests on the assumption of a significant student engagement in the research of the real life problems. As an innovative model, it implies a focus shifting from receptive learning that prevails in traditional teaching to active construction of knowledge, which determine various changes in teaching practice. Any change in the established practice can pose numerous difficulties, problems, doubts, open questions, and other challenges to participants in the teaching process. Therefore, the aim of this qualitative study was to examine the experience of teachers regarding the challenges they face during the preparation and implementation of the projectbased learning. The research was conducted during the school year 2023/24 and nine primary and secondary school teachers from Serbia took part in it – four from primary schools, two from vocational secondary schools, and three from high schools. The technique of a synchronous online focus group interview was used, which was recorded and the data were transcribed. Data analysis was performed using the qualitative method of inductive-type thematic analysis. Determining the project topic, forming teacher teams and selecting students who will participate in the project were identified as the key challenges faced by teachers in preparing project-based learning. The teachers stated that their challenges during the implementation of the project-based learning included the time spent, opportunities for learning, and the attitude of others towards project-based learning. It was concluded that the perceived challenges should not discourage teachers, but should serve as a starting point for a deeper analysis and improvement of one’s own practice in the field of preparation and application of project-based learning.